Combining Ability for Grain Yield and its Related Traits in Pearl Millet [Pennisetum glaucum (L.)R. Br.]: Combining ability in pearl millet for yield - Sharma, Shravan; Solanki, Kanti Lal; Gupta , P C (Annals of Arid Zone, 2023)
Combining ability analysis for grain yield and its contributing characters was carried out among ten female lines from diverse cytoplasmic male sterility sources, five elite restorers and 50 hybrids through Line x Tester mating design. The magnitude of SCA variances was higher than the GCA variances for all the characters, which indicated predominance of non-additive gene action in the inheritance of these traits and it was further supported by less magnitude of σ2 gca / σ2 sca ratios. Among the females RMS 6A, ICMA 92777 and JMSA 20073 while among the malesH77/833-2 and RIB 57SO5 were good general combiner for seed yield and most of the component characters. The cross combinations JMSA 20073 × RCB-IC 925 S3 19-3-1, ICMA 04999 × H77/833-2 and RMS 6A × MIR 97092-2-4 depicted significant and desirable SCA effects for most of the traits studied. In thepresent investigations two crosses ICMA 92777 × H77/833-2 and JMSA 20073 × H77/833-2 were identified for getting trangressive segregants as the GCA status of the parents is higher than the SCA effects. These hybrids can be recommended for wide spread cultivation in arid part of western Rajasthan after evaluation in multi-locational trails for increasing pearl millet production and productivity.